Spectral and laboratory data for boiled cassava in Colombia - Tran, Thierry; Escobar Salamanca, Andres Felipe (2023)
This file contains spectral and laboratory data for boiled cassava that was collected by CIAT team in Colombia following standard operating procedures. (2022-8-19)